PERAN PENYULUH TERHADAP ADOPSI INOVASI PETERNAK AYAM KAMPUNG DI KECAMATAN TOMOHON BARAT - Mangundap, Viane; Rintjap, A K; Sajow, A A; Tumewu, J (ZOOTEC, 2020)
THE ROLE OF EXTENSION TO THE ADOPTION OF FARMERS INNOVATION IN THE DEVELOPMENT OF WEST TOMOHON DISTRICT TOMOHON CITY. Study was conducted on December 2019 to evaluate the role extension in the adoption of smallholder innovation in development of native chicken at West Tomohon District. This research was a survey using questionnaires. Samples were determind by purposive sampling method involving 30 smallholder of local native chicken. Chi square method was used to analyze the data. The role of extension was meansured by ordinal scale for questions given to breeders and the adoption of innovation was measured by ordinal scale of the level of knowledge, attitudes and skills of native chicken farmers. Knowledge was divided into several categories, namely high, medium and low knowledge, the attitude of the category accepts innovation, it is enough to accept innovation and reject innovation, the skill of the category was skilled, sufficiently skilled and unskilled. The results of the study used Chi-Square analysis showed that the role of extension workers had a significant relationship with the attitudes of native chicken farmers while on the other hand the role of extension workers did not not have a significant relationship with the knowledge and skills of native chicken farmers.